Asymmetric aza-Morita–Baylis–Hillman reactions of chiral N-phosphonyl imines with acrylates via GAP chemistry/technology. Issue 25 (27th May 2016) - Yang, Bing; Ji, Xiaozhou; Xue, Yunsheng; Zhang, Haowei; Shen, Minxing; Jiang, Bo; Li, Guigen
Abstract : A series of aza-Morita–Baylis–Hillman acrylates have been synthesized by using chiral N -phosphonyl imines and GAP chemistry/technology. Abstract : Chiral N -phosphonyl imines have been proven to be efficient electrophilic acceptors for asymmetric aza-Morita–Baylis–Hillman (aza-MBH) reactions with acrylates under convenient conditions. Thirty examples of β-amino acrylates were generated in high yields (up to 99.4%) and diastereoselectivity (up to >99 : 1 dr) in an atom-economical fashion. The synthesis was proved to follow the GAP (group-assisted purification) chemistry, i.e., the pure products can be obtained simply by washing the crude products with hexane/ethyl acetate (v/v, 10/1) without the use of chromatography or recrystallization. DFT calculations were also conducted to support an asymmetric induction model accounting for high diastereoselectivity.